2020
DOI: 10.1186/s12862-020-1590-1
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of sweet taste receptor genes in grass carp (Ctenopharyngodon idellus) coincided with vegetarian adaptation

Abstract: Background: Taste is fundamental to diet selection in vertebrates. Genetic basis of sweet taste receptor in the shaping of food habits has been extensively studied in mammals and birds, but scarcely studied in fishes. Grass carp is an excellent model for studying vegetarian adaptation, as it exhibits food habit transition from carnivory to herbivory. Results: We identified six sweet taste receptors (gcT1R2A-F) in grass carp. The four gcT1R2s (gcT1R2C-F) have been suggested to be evolved from and paralogous to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
3
7
0
Order By: Relevance
“…Hence, gene expression was quantified by qPCR in different tissues within oropharingeal, GIT and brain regions. Our findings are in accordance with previous studies that reported several taste receptors and taste signaling components in the GIT of different fish species ( Polakof and Soengas, 2013 ; Latorre et al., 2013 ; Ronnestad et al., 2016 ; Yuan et al., 2020 ; Calo et al., 2021 ; Kinnamon, 2012 ; Morais, 2017 ), reinforcing the hypothesis that the T1R-mediated gut sensing mechanisms could be conserved throughout vertebrate evolution. The significantly higher levels of sa T1R3 expression observed in oropharyngeal and GIT tissues suggest that this gene might be locally demanded at higher transcriptional rates due to heterodimerization with sa T1R1 or sa T1R2 subunits, since sa T1R3 / sa T1R3 homodimers do not seem to respond to L-amino acids stimulations in this species ( Angotzi et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, gene expression was quantified by qPCR in different tissues within oropharingeal, GIT and brain regions. Our findings are in accordance with previous studies that reported several taste receptors and taste signaling components in the GIT of different fish species ( Polakof and Soengas, 2013 ; Latorre et al., 2013 ; Ronnestad et al., 2016 ; Yuan et al., 2020 ; Calo et al., 2021 ; Kinnamon, 2012 ; Morais, 2017 ), reinforcing the hypothesis that the T1R-mediated gut sensing mechanisms could be conserved throughout vertebrate evolution. The significantly higher levels of sa T1R3 expression observed in oropharyngeal and GIT tissues suggest that this gene might be locally demanded at higher transcriptional rates due to heterodimerization with sa T1R1 or sa T1R2 subunits, since sa T1R3 / sa T1R3 homodimers do not seem to respond to L-amino acids stimulations in this species ( Angotzi et al., 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, there were significantly higher mRNA levels of both sa T1R2b and sa T1R2f than sa T1R2a / T1R2d / T1R2e in gills. These gene expression patterns are in agreement with those recently described for T1R2b / e ortholog counterparts in grass carp ( Ctenopharyn godonidellus ) ( Yuan et al., 2020 ), suggesting that the T1R2-mediated chemosensing functions may have been highly retained in gills throughout teleost radiation. We found also high levels of expression for the paralog subtypes sa T1R2d / e and sa T1R2d / e / f in forebrain and hindbrain, respectively, suggesting that these genes might have a tissue-specific chemosensory role in these brain compartments.…”
Section: Discussionsupporting
confidence: 90%
“…These genes were collected either from published studies or by against species genome for functions by generating umami, sweet and bitter tastes (Figure 6). 132–135 In grass carp, expanded T1R2s (gene copy numbers = 6) were found compared to other herbivorous fish. Gene expansion was also observed in another herbivorous Indian major carp compared with others.…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 9, 2023. ; https://doi.org/10.1101/2023.04.08.532961 doi: bioRxiv preprint only T1R2A/T1R3A is responsible for sugar perception in mammals and reptiles 24 , we previously demonstrated that T1R1/T1R3A of birds has gained the ability to detect sugars 25,26 . Also, T1R2B/T1R3B of two teleost fishes, namely carp 27 and gilthead seabream 28 , can detect sugars at high concentrations (100-200 mM). In addition, we found that bichir T1R7/T1R4 could respond to GMP, although a previous study reported that neither T1R1/T1R3B nor T1R2B/T1R3B of medaka fish nor T1R2B/T1R3B of zebrafish could be activated by 5'-ribonucleotides 10 .…”
Section: T1r Diversity Enhances the Range Of Taste Sensationmentioning
confidence: 99%